Strategy Competitive Advantages through Marketing Performance - Arumsari, Nurul Rizka; Marka, Mira Meilia (KINERJA, 2018)
This study aims to describe efforts to create competitive advantages through marketing performance based on product innovation and promotion on SMEs weaving Troso in Jepara district. The research method used is multiple linear regression analysis 2 stages with sampling technique using purposive sampling. The results showed that product innovation as measured by three indicators covering product line, new product, and artificial product have a positive and significant influence on marketing performance. Promotions measured by six indicators covering advertising, personal selling, sales promotion and publicity have proven to have a positive and significant impact on marketing performance. Marketing performance measured by three indicators that include profit targets, customer growth, and sales turnover have a positive and significant impact on competitive advantage.Keywords: competitive advantage, marketing performance, product innovation, promotion